2011
DOI: 10.1097/phm.0b013e318214ed0d
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Total End Range Time is Safe and Effective for the Conservative Treatment of Frozen Shoulder Patients

Abstract: We conclude that a total end range time-maximizing rehabilitation protocol is a safe, effective treatment option for patients with frozen shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Similar results with the same HIS device used in this study have been reported with shoulder hypomobility [29]. In that study, patients with idiopathic or postoperative adhesive capsulitis who had reached a plateau in their recovery received outpatient PT plus the same adjunct HIS therapy as in the current study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results with the same HIS device used in this study have been reported with shoulder hypomobility [29]. In that study, patients with idiopathic or postoperative adhesive capsulitis who had reached a plateau in their recovery received outpatient PT plus the same adjunct HIS therapy as in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Patients were classified by the irritability criteria suggested by Kelley et al (Table 2) [35]. It was suggested that HIS could be disadvantageous for patients with high irritability, but in the study by Dempsey et al [29], all patients showed significantly improved ASES scores and external rotation ROM and abduction ROM, regardless of irritability status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this assessment, to restore the rom and function of the shoulder, with the reestablishment of the scapulo-humeral rhythm we designed a multi-approach protocol combining effective strategies already used by other authors, such as laser therapy , low load prolonged stretch , exercise therapy, trigger point therapy and manual therapy [33,19,[34][35][36]. In the current case report, the treating clinicians utilized a deep pressure soft tissue mobilization technique in conjunction with lllt.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been reported llps, within each patient´s tolerance level, into various rotation restrictions may result in safe, effective and timely return to elevation rom [1,19]. nevertheless, it is important to note in which phase of adhesive capsulitis the patient is to decide to whether use the technique or not since the chosen intensity must allway be "beneath the pain threshold".…”
Section: Introductionmentioning
confidence: 99%